Scaling Week 2024 - CGIAR System Organization; Schneidt, Agnes; MacMillan, Susan; Buono, Nicoletta (CGIAR System Organization, 2025)
In December 2024, CGIAR's Third Annual Week on the Science and Practice of Scaling Agrifood Innovations took place, attracting more than 70 experts to the campus of the International Livestock Research Institute (ILRI) in Nairobi, Kenya. This event was organized by the CGIAR Research Initiative on Diversification in East and Southern Africa (“Ukama Ustawi”), the CGIAR Portfolio Performance Unit (PPU), and ILRI. This summary distills the key outcomes and insights from the event and captures its collaborative spirit and strategic discussions.